Integrating the Javanese Local Tradition of Selametan into History Learning Projects to Strengthen the Profile of Pancasila-Based Student Character - Wilis, Roro; Kinanti, Ajeng Diah; Kumalasari, Dyah (Jurnal Pendidikan Progresif, 2025)
Integrating the Javanese Local Tradition of Selametan into History Learning Projects to Strengthen the Profile of Pancasila-Based Student Character . Objectives: This study aims to explore the history and perspectives of the Javanese community in viewing local selametan traditions and character values relevant to the Profile of Pancasila-Based Student Character. This research also analyses how history teachers can internalise these character values in learning that is integrated with the local selametan tradition. Methods: This research uses a qualitative case study design with data collection techniques through non-participatory observation, in-depth interviews, document analysis, and literature review. The consideration for selecting a single case study design focused on SMA Negeri 9 Yogyakarta was not only based on the implementation of Project-Based Learning (PjBL) in history integrated with the local Javanese tradition of selametan, but also on the uniqueness of the school, which claims to be The Art and Cultural School. Content analysis was used to interpret secondary data related to history and the meaning of the local selametan tradition. Additionally, the single case study design was employed to explore how the internalisation of character values occurs in history learning practices. Sampling techniques were conducted using purposive sampling, considering exclusion and inclusion criteria, involving several subjects such as the Vice Principal for Curriculum, history teachers, and student representatives from grade X at State Senior High School 9, Yogyakarta. Data validity and reliability were obtained through source triangulation techniques and analysed using an interactive model. Findings: The findings indicate that the local tradition of selametan has an important position in the perspective of the Javanese community, is relevant to the history material on Community Life in the Indonesian Archipelago during the Islamic Period, and contains character values that are in line with the Profile of Pancasila-Based Student Character (P5), namely religious, critical thinking, global diversity, independence, creativity, and cooperation. To internalise these character values, the researcher utilised three stages of development proposed by Thomas Lickona, encompassing moral knowledge, moral feelings, and moral actions. Conclusion: The Project-Based Learning (PjBL) model integrated with the local Javanese tradition of selametan serves as a historical learning design that not only enhances students' cognitive understanding but also has the potential to positively impact the development of character traits aligned with the Profile of Pancasila-Based Student Character (P5). Keywords: contextual, local java tradition, selametan, project-based learning, history learning.